The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1590/1413-7054202044003220
|View full text |Cite
|
Sign up to set email alerts
|

Maltodextrin on the flow properties of green coconut (Cocos nucifera L.) pulp powder

Abstract: The study of the flow properties and particle surfaces of a food powder is essential for predicting its behaviour during processing and commercialization. The objective of this work was to determine the powder flow properties of lyophilized green coconut pulp with different concentrations of maltodextrin. Samples containing 0, 5, 10 and 15% (m/m) maltodextrin were lyophilized, and the flow index (FI), wall friction angles and densities were determined. The microstructure of the powders was evaluated by scannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 28 publications
(27 reference statements)
1
5
0
Order By: Relevance
“…The type of carrier and concentration will influence the friction angle Seerangurayar et al (2017),. when comparing the addition of maltodextrin and Arabic gum, verified the smallest angles in powders containing Arabic gum, as in the present study Araújo et al (2020). observed a reduction of wall friction angles in the powders of green coconut pulp with the increase in carrier concentration, obtaining values between 15.8 and 39.8 .4 | CONCLUSIONSThe use of drying carriers influenced the content of total polyphenols in sapodilla pulp powder.…”
supporting
confidence: 85%
See 4 more Smart Citations
“…The type of carrier and concentration will influence the friction angle Seerangurayar et al (2017),. when comparing the addition of maltodextrin and Arabic gum, verified the smallest angles in powders containing Arabic gum, as in the present study Araújo et al (2020). observed a reduction of wall friction angles in the powders of green coconut pulp with the increase in carrier concentration, obtaining values between 15.8 and 39.8 .4 | CONCLUSIONSThe use of drying carriers influenced the content of total polyphenols in sapodilla pulp powder.…”
supporting
confidence: 85%
“…Seerangurayar et al (2017), when comparing the addition of maltodextrin and Arabic gum, verified the smallest angles in powders containing Arabic gum, as in the present study. Araújo et al (2020) observed a reduction of wall friction angles in the powders of green coconut pulp with the increase in carrier concentration, obtaining values between 15.8° and 39.8°.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations